(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Review the initial results of applying ECMO - VV for treating patients with severe acute respiratory distress syndrome (ARDS) at Intensive Care Department of National Lung Hospital in 2023. Method: Case-series study design, performed on 13 patients with severe ARDS who were technique applied ECMO - VV at the Intensive Care Department of National Lung Hospital. Results: 13 ARDS patients were treated with ECMO - VV technique at Intensive Care Department of National Lung Hospital in 2023. The study describes a series of cases. The average age is 53.6 ± 13.5 years old, men account for 8/13. Before ECMO - VV intervention, the average SOFA score was 6.77 ± 1.83. The median duration of ECMO intervention is 5 days, the longest period is 30 days. The most common complications are thrombocytopenia (<80G/l): 9 patients (69.2%); new infections after 48 hours of EMCO treatment, 8 patients (61.5%). Conclusions: 7 patients (53.8%) were successfully weaned off ECMO. The rate of survival is 6/13. Conclusion: ECMO - VV is a necessary technique to ensure blood oxygenation for severe ARDS patients, is effective in treating the causes of acute respiratory failure.